Analysing Oral Fossilisation in a Pre-Intermediate Business English Class: A Case Study - Pelawi, Rinawati (Foremost Journal, 2025)
This study analyses the phenomenon of oral fossilisation in a pre-intermediate Business English class. The study examines six pre-intermediate Business English class participants to identify persistent language errors and evaluate the effectiveness of targeted instructional strategies. Fossilisation, defined as the persistence of incorrect linguistic forms despite exposure to correct usage, poses significant challenges in language learning, particularly in professional contexts. The data were gathered through class observations and field note-taking during six sessions or 12 hours. The findings revealed persistent grammatical errors such as incorrect verb tense usage, double verb usage, errors in subject-verb agreement and article omissions, and lexical challenges, including inappropriate word usage and pronunciation issues. While targeted instructional strategies—such as role-playing, contextualised grammar exercises, and pronunciation drills—resulted in modest improvements, many errors remained resistant to correction. The study underscores the importance of individualised feedback, extended practice opportunities, and authentic communicative tasks in addressing fossilisation. These findings have implications for designing more effective Business English curricula to foster greater oral proficiency in workplace communication.